Impact of Non-Financial Drivers on Job Satisfaction and Their Influence on the Sustainability of Startups and Small Businesses in Saudi Arabia (The International Journal for Scientific Research, 2024)
This research investigates the impact of non-monetary factors on employee satisfaction and how these factors contribute to the sustainability and growth of startups and small businesses in Saudi Arabia. Recognizing the financial constraints often faced by these companies, the study emphasizes the importance of non-monetary incentives—such as work-life balance, recognition, career development opportunities, and a positive organizational culture—in enhancing employee satisfaction. Through a quantitative approach involving a sample of 51 participants, the research identifies key non-monetary drivers that influence job satisfaction and examines their relationship with organizational performance, employee retention, and overall business success. The findings highlight that factors like recognition and career advancement are crucial for fostering a motivated and committed workforce, which is essential for the long-term sustainability of startups and small businesses. The study contributes to the broader discourse on employee satisfaction within the context of Saudi Arabia's evolving entrepreneurial landscape and offers actionable recommendations for business leaders and policymakers to support the sustainability and growth of these enterprises, in alignment with the goals of Saudi Vision 2030.
Keywords: Job Satisfaction; Sustainability; Startups Businesses; Small Businesses; Saudi Arabia